SINKRONISASI KEBIJAKAN KERJASAMA ANTAR DAERAH DALAM DIVESTASI SAHAM PT NEWMONT NUSA TENGGARA - Lalu Pria Wira S. (Mimbar Hukum, 2015)
Divestment of PT NNT is located in the province of NTB, involving three Local Government ie Province, KSB, and Sumbawa regency, and have collaborated to form PT DMB is partnering with PT MC to acquire PT NNT. As a result of that happening is disagreement between the three regions in issuing policies on regional cooperation. To that end, the synchronization policy research cooperation between the three parties, including the central government needs to be done to avoid disharmony between regions that are not infrequently involve the community.